An energy-efficient SDN based sleep scheduling algorithm for WSNs. (January 2016) - Wang, Yanwen; Chen, Hainan; Wu, Xiaoling; Shu, Lei
Abstract: Energy efficiency in Wireless Sensor Networks (WSNs) has always been a hot issue and has been studied for many years. Sleep Scheduling (SS) mechanism is an efficient method to manage energy of each node and is capable to prolong the lifetime of the entire network. In this paper a Software-defined Network (SDN) based Sleep Scheduling algorithm SDN-ECCKN is proposed to manage the energy of the network. EC-CKN is adopted as the fundamental algorithm when implementing our algorithm. In the proposed SDN-ECCKN algorithm, every computation is completed in the controller rather than the sensors themselves and there is no broadcasting between each two nodes, which are the main features of the traditional EC-CKN technique. The results of our SDN-ECCKN show its advantages in energy management, such as network lifetime, the number of live nodes and the number of solo nodes in the network.